Pengaruh Iklan Berdasarkan Konsep AIDA Terhadap Keputusan Pembelian Sabun Mandi Lifeboy (Studi Kasus Pada Warga Depok-Jawa Barat) - Nurmin Arianto (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
This study aims to determine the influence of attention, interest, desire, action against the decision of the purchase. And influence together. This research was conducted on the residents of the city of Depok in with incidental sampling technique. Research methods associative quantitative. By using data analysis testing instrument, the classical assumption test and multiple linear regression. From the results of the research variables, namely attention, interest, desire and action has significant influence on purchasing decisions either partially or together. And the most influential variable on purchasing decisions is the desire.